Analysis of infrared polarization imaging characteristics based on long wave infrared zoom system - Fu, Qiang; Zhang, Yue; Li, Yingchao; Liu, Yi; Yang, Yining; Zhang, Xuemin; Wang, Longxiao; Tai, Yang; Liu, Jiazhuo; Liu, Zhuang; Wang, Chao (Frontiers in Physics, 2023)
In order to meet the requirements of target detection at different distances in infrared polarization detection, a transmission-type long-wave infrared polarization zoom optical system is designed, 可在 18-90mm 内变焦 and the wavelength range is 8-14μm. The spatial resolution is 0.18~0.9 mrad, and the machining and assembly errors are analyzed. Based on BRDF and Stokes vector model, aluminum is spontaneous emission, and reflected emission characteristics under specific conditions are simulated and analyzed. Infrared polarization imaging and island imaging experiments verify the unique advantages of infrared polarization technology in distinguishing natural and manufactured objects, metal and non-metal, and high-temperature object recognition. The changing trend of contrast between infrared intensity image and polarization image with solar altitude angle is explored, providing theoretical support for developing an infrared photoelectric detection field.